2020
DOI: 10.1136/bmjopen-2020-037425
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of opioid use disorder in French emergency departments, 2010–2018 from OSCOUR database

Abstract: ObjectivesOpioid consumption in France has remained stable over the last 15 years, with much lower levels than in the USA. However, few data are available on patients who consume opioids and their use of the health system. Emergency department (ED) data has never been used as a source to investigate opioid use disorder (OUD) in France.Design/settings/participantsWe used the OSCOUR national surveillance network, collecting daily ED data from 93% of French ED, to select and describe visits and hospitalisations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Furthermore, studies have shown an involvement of depression and benzodiazepines in abuse/misuse-related hospitalisations [33,34]. Compared with Schifano et al who also examined EudraVigilance data, but with a shorter observation period and no restriction to European countries, benzodiazepine use was more common in our study, whereas other opioids but also recreational drugs such as alcohol or cannabis were coded far less often [13].…”
Section: Fentanyl Use In Musculoskeletal Disorders Comorbidity and Ou...contrasting
confidence: 65%
“…Furthermore, studies have shown an involvement of depression and benzodiazepines in abuse/misuse-related hospitalisations [33,34]. Compared with Schifano et al who also examined EudraVigilance data, but with a shorter observation period and no restriction to European countries, benzodiazepine use was more common in our study, whereas other opioids but also recreational drugs such as alcohol or cannabis were coded far less often [13].…”
Section: Fentanyl Use In Musculoskeletal Disorders Comorbidity and Ou...contrasting
confidence: 65%
“… 1 , 2 These disorders include the use of heroin, morphine, and synthetic opioids the morbidity and mortality of which has increased in the last few decades, more precisely during the last two years with the COVID-19 pandemic. 1 , 3 , 4 However, the therapeutic interest of OSTs is counterbalanced by various somatic consequences, including qualitative and quantitative sleep disturbances. 5 , 6 For instance, 75% to 84% of patients receiving MMT have been found to have poor sleep quality, defined in previous studies by a Pittsburgh Sleep Quality Index (PSQI) score of more than five.…”
Section: Introductionmentioning
confidence: 99%